Contentions of affordability in the habitat planning of a new town - Ramakrishna, Bhagyasshree (2023)
The onus of re-constructing a diverse socio-spatial and economically-prepared urban framework in the design of greenfield cities rests on the foresight of a Master Plan document. The conceptualisations in the making of a ‘brand-new city’ are challenged with its subsequent realisation. Often, urbanisation doesn’t tread its planned course, and contentious dualities of planned vs unplanned persists. In Navi Mumbai, five decades later, small-scale slum-settlements emerge as landscapes of dispossession and inevitable gentrification creating urban ruptures within the city morphology. Navi Mumbai was an expression of India’s euphoria as a newly independent nation, exemplified by pragmatic city planning. However, five decades later, the emergence of planning disruptions continues to indicate inadequacies. The paper examines the spatial logics of habitation under changing economic conditions and built-in spatial inequalities. It initiates a discourse on the type of environments planned cities foster towards residents from lower economic and social backgrounds. The key research questions addressed are: How do master plans further socio-economic segregations? What was the impact of neoliberal changes on affordable housing? Points of critique: Navi Mumbai’s reliance on ‘Euro-American’ visions and Fordist planning present several delinkages with adjacent industrial districts, indigenous farming settlements and sensitive ecological edges. The analysis conferred that affordable housing schemes became an unequal instrument of social cohesion, in light of built-in inequities. The Development Plan of Navi Mumbai excluded its original inhabitations- agricultural and fishing villages, a characteristic adopted by several development plans in contemporary Indian cities. Close examination of mechanisms of ‘incrementality’, as a hall-mark of affordable housing projects, suggests disconnections between designer’s vision and dweller’s aspirations.